The effect of hydrothermal and acid dealumination on the structural, acid and catalytic properties of Mordenite - O'Donovan,Anthony William (Department of Chemical Engineering, 2016)
Although there have been a number of studies of the effect of hydrothermal and acid dealumination on the properties of Mordenite, there is a lack of clarity on many issues related to the changes which these treatments cause to the structure, acidity and catalytic activity of Mordenite. Both methods remove aluminium from the framework thus creating extra framework aluminium species. Although there are some reports that these species, particularly when created by mild steaming, increase the acidity and catalytic activity of the dealuminated sample, it has also been reported that these species have either a negative or no effect on thecatalyst's acidity and activity [Mirodatos and Barthomeuf, 1981; Chen eta/., 1992; Meyerseta/., 1988; Bamwenda eta/., 1994; Brunner eta/., 1994]. These conflicting reports are understandable when one considers that the dealumination conditions in the various studies are usually not equivalent to each other and consequently the resultant catalysts may differ. The use of Mordenite from different sources to compare acidity in one case and structure in another may also lead to different and conflicting results. This has affected the interpretation of observed trends in the structure, acidity and catalytic behaviour of dealuminated Mordenite. A systematic study of the effect of acid washing of sodium Mordenite and hydrogen exchanged Mordenite, both before and after steaming, has been carried out. The bulk removal of aluminium was monitored by elemental analysis of samples. The study investigated the effect of different conditions of acid washing, steaming and steaming followed by acid washing on the solid state properties of Mordenite by use of solid state ²⁷AI and ²⁹Si nuclear magnetic resonance, x-ray diffraction and infrared techniques. The effect of these changes on the number, type and strength of acid sites in Mordenite was then investigated by ammonia temperature programmed desorption, Fourier-Transform infrared analysis of pyridine adsorption and proton nuclear magnetic resonance studies. The changes caused by dealumination to the catalytic activity and shape selective properties of Mordenite as determined by studies of isobutane cracking, cyclohexanol dehydration and isopropylation of naphthalene, were then explained in terms of the acidic and structural properties of the dealuminated Mordenite samples.